Prediction of Stable Composition for High-Entropy Refractory Alloys - Melnick, A.B.; Soolshenko, V.K. (Металлофизика и новейшие технологии, 2016)
The common approach for evaluation of stability of multicomponent substitutional solid solutions using thermodynamic, mechanical, and topological parameters of the constituent elements is developed. The high-temperature systems based on refractory elements (W, Ta, Mo, Nb, V, Ti, Zr, Hf, Cr) are investigated using this approach. Optimal compositions for high-entropy alloys are obtained, and influence of various factors in the formation of stable alloys is described. As shown, the most resistant alloys have non-equiatomic element-contents’ ratios. The agreement between element distribution in experimental alloys and predicted stable compositions are obtained for the W— Ta—Mo—Nb and W—Ta—Mo—Nb—V systems. Розроблено загальний підхід для оцінки стабільности багатокомпонентних твердих розчинів заміщення з використанням термодинамічних, механічних і топологічних параметрів елементів, що їх складають. Високотемпературні системи, що містять тяжкотопкі елементи (W, Ta, Mo, Nb, V, Ti, Zr, Hf, Cr), були досліджені за допомогою цього підходу. Одержано оптимальні склади для високоентропійних стопів і описано вплив різних чинників у формуванні стабільних стопів. Показано, що найбільш стійкі стопи мають нееквіатомне співвідношення складів елементів. Для систем W—Ta—Mo—Nb і W—Ta—Mo—Nb—V було одержано узгодженість між розподілами елементів в експериментальних стопах і прогнозованих стабільних композиціях. Разработан общий подход для оценки стабильности многокомпонентных твёрдых растворов замещения с использованием термодинамических, механических и топологических параметров составляющих их элементов. Высокотемпературные системы, состоящие из тугоплавких элементов (W, Ta, Mo, Nb, V, Ti, Zr, Hf, Cr), были исследованы с использованием этого подхода. Получены оптимальные составы для высокоэнтропийных сплавов и описано влияние различных факторов при формировании стабильных сплавов. Показано, что наиболее стабильные сплавы характеризуются неэквиатомным отношением составов элементов. Для систем W— Ta—Mo—Nb и W—Ta—Mo—Nb—V было получено согласие между распределениями элементов в экспериментальных сплавах и предсказанных стабильных композициях.